2018
DOI: 10.18311/jeoh/2018/20017
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Usage and its Applications among School Going Children (5-16 Years) in Lahore, Pakistan

Abstract: Objective: To analyze the most used applications on smartphone among school going children (5-16 years). Study Design and Setting: Descriptive cross sectional study comprised of five months (April 2017 to July 2017); concerned community survey i.e. door to door data collection method was carried out in Lahore, Pakistan. Material and Methods: Multistage cluster sampling technique was used. 6200 school going children were selected, 4030 (65%) respond to the study and remaining 2170 (35%) do not respond to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…While one study reported that students from higher-income families spent more time on their mobile phones [ 21 ], another found that lower-income students used their mobile phones more often [ 22 ]. In a study conducted in Pakistan, the majority of students aged 5–16 years old (69%) reported ST device use of less than 2 h per day [ 23 ]. Perhaps the lifestyles and economic statuses of the people in these studies are the factors behind this difference in ST device use.…”
Section: Discussionmentioning
confidence: 99%
“…While one study reported that students from higher-income families spent more time on their mobile phones [ 21 ], another found that lower-income students used their mobile phones more often [ 22 ]. In a study conducted in Pakistan, the majority of students aged 5–16 years old (69%) reported ST device use of less than 2 h per day [ 23 ]. Perhaps the lifestyles and economic statuses of the people in these studies are the factors behind this difference in ST device use.…”
Section: Discussionmentioning
confidence: 99%
“…Duggan et al (2015) found that two and more SNSs were used by people, therefore, focusing on one SNS is problematic. The results of the study have shown that despite the low-income country and culturally collectivists, still, the trends of social media usage are higher in Pakistan (Tariq et al, 2018). Since Pew Research Center also reported accelerating use of social media technologies in developing the region and the presented studies also indorsed the growing use.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, it is imperative to test empirically the growing use of SNSs and validate an instrument to measure duration, needs, and motives for SNSs use in developing countries and in their social context. Like other developing countries, rapid adoption of technologies, such as smartphones and SNSs is observed in Pakistan (Tariq, Tariq, Hussain, & Shahid, 2018).…”
Section: Background Of the Current Studymentioning
confidence: 99%
“…According to another study conducted in Pakistan on school going children found significant association between long-term smartphone usage with behavioural and psychological problems. 16 Another study has mentioned that Television is most watched screen-based device among children. 17 television is the device that was most watched by preschoolers (n=119, 59.5%).…”
Section: Discussionmentioning
confidence: 99%
“…According to another study conducted in Pakistan on school going children found significant association between long-term smartphone usage with behavioural and psychological problems. 16 …”
Section: Discussionmentioning
confidence: 99%